2019
DOI: 10.3390/ijms20246134
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Proliferation Is Induced by Chronically TLR2-Stimulated Gingival Fibroblasts or Monocytes

Abstract: During inflammation of the gums, resident cells of the periodontium, gingival fibroblasts (GFs), interact with heterogeneous cell populations of the innate and adaptive immune system that play a crucial role in protecting the host from pathogenic infectious agents. We investigated the effects of chronic inflammation, by exposing peripheral blood mononuclear cells (PBMCs), peripheral blood lymphocyte (PBL) cultures, and GF–PBMC cocultures to Toll-like receptor 2 (TLR2) and TLR4 activators for 21 days and assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…We previously described, that TLR activation results in the production of inflammatory cytokines ( 24 ). We next measured TNF-α in the supernatant of GF-PBMC co-cultures ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously described, that TLR activation results in the production of inflammatory cytokines ( 24 ). We next measured TNF-α in the supernatant of GF-PBMC co-cultures ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…TLR2 and TLR4 are expressed in the periodontal tissues, and among them on GF ( 23 , 24 ). GF play an important role in processes associated with bone remodeling such as the induction and inhibition of osteoclast formation ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next day (day 0), 0.5 × 10 6 peripheral blood mononuclear cells (PBMCs) were seeded on top. The PBMCs were isolated from the buffy coat (Sanquin, Amsterdam, The Netherlands) by a standard density gradient centrifugation with Ficoll-Paque [ 35 ]. Co-cultures of bone cells and PBMCs were cultured for up to 21 days in basic medium (same composition as the basic medium in the osteogenesis experiments) or the basic medium supplemented with 10 nM vitD 3 .…”
Section: Methodsmentioning
confidence: 99%
“…One of the vital recognition systems for microbial dysbiotic change is toll-like receptors (TLR). Moonen et al reported that activation of TLR2 in gingival fibroblasts or monocytes is responsible for the T cell proliferation [ 2 ]. Consistent with this study, it has long been demonstrated that the TLR-mediated innate immune system by pathogen-associated molecular patterns (PAMPs) activates T and B cells’ immune responses to produce inflammatory cytokines and elicits osteolytic pathways, promoting periodontal inflammation and bone resorption.…”
mentioning
confidence: 99%